Physical properties of the magnetically frustrated very-heavy-fermion compound YbCu4Ni - Sereni, J.G. (2018)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina